CAR-T cell therapy in triple-negative breast cancer: Hunting the invisible devil - Nasiri, Fatemeh; Kazemi, Mehrasa; Mirarefin, Seyed Mohamad Javad; Mahboubi Kancha, Maral; Ahmadi Najafabadi, Milad; Salem, Faeze; Dashti Shokoohi, Setareh; Evazi Bakhshi, Sahar; Safarzadeh Kozani, Pouya; Safarzadeh Kozani, Pooria (Frontiers in Immunology, 2022)
Triple-negative breast cancer (TNBC) is known as the most intricate and hard-to-treat subtype of breast cancer. TNBC cells do not express the well-known estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 (HER2) expressed by other breast cancer subtypes. This phenomenon leaves no room for novel treatment approaches including endocrine and HER2-specific antibody therapies. To date, surgery, radiotherapy, and systemic chemotherapy remain the principal therapy options for TNBC treatment. However, in numerous cases, these approaches either result in minimal clinical benefit or are nonfunctional, resulting in disease recurrence and poor prognosis. Nowadays, chimeric antigen receptor T cell (CAR-T) therapy is becoming more established as an option for the treatment of various types of hematologic malignancies. CAR-Ts are genetically engineered T lymphocytes that employ the body’s immune system mechanisms to selectively recognize cancer cells expressing tumor-associated antigens (TAAs) of interest and efficiently eliminate them. However, despite the clinical triumph of CAR-T therapy in hematologic neoplasms, CAR-T therapy of solid tumors, including TNBC, has been much more challenging. In this review, we will discuss the success of CAR-T therapy in hematological neoplasms and its caveats in solid tumors, and then we summarize the potential CAR-T targetable TAAs in TNBC studied in different investigational stages.